Targeting autophagy in colorectal cancer: An update on pharmacological small-molecule compounds. Issue 8 (August 2022) - Li, Zixiang; Si, Wen; Jin, Wenke; Yuan, Zhaoxin; Chen, Yi; Fu, Leilei
Graphical abstract: Highlights: Autophagy plays the Janus role in colorectal cancer (CRC). Autophagy-associated cell death and cytoprotective autophagy are involved in carcinogenesis. Small-molecule compounds modulate autophagy-associated cell death or cytoprotective autophagy in CRC. Targeting of autophagy is a potential strategy for the discovery of drugs to treat CRC. Abstract: Autophagy, an evolutionarily highly conserved cellular degradation process, plays the Janus role (either cytoprotective or death-promoting) in colorectal cancer, so the targeting of several key autophagic pathways with small-molecule compounds may be a new therapeutic strategy. In this review, we discuss autophagy-associated cell death pathways and key cytoprotective autophagy pathways in colorectal cancer. Moreover, we summarize a series of small-molecule compounds that have the potential to modulate autophagy-associated cell death or cytoprotective autophagy for therapeutic purposes. Taken together, these findings demonstrate the Janus role of autophagy in colorectal cancer, and shed new light on the exploitation of a growing number of small-molecule compounds to target autophagy in future cancer drug discovery.